Beyond membrane channelopathies: alternative mechanisms underlying complex human disease - Boudoulas Konstantinos Dean; Mohler Peter J (Acta Pharmacologica Sinica, 2016)
Over the past fifteen years, our understanding of the molecular mechanisms underlying human disease has flourished in large part due to the discovery of gene mutations linked with membrane ion channels and transporters. In fact, ion channel defects (“channelopathies” — the focus of this review series) have been associated with a spectrum of serious human disease phenotypes including cystic fibrosis, cardiac arrhythmia, diabetes, skeletal muscle defects, and neurological disorders. However, we now know that human disease, particularly excitable cell disease, may be caused by defects in non-ion channel polypeptides including in cellular components residing well beneath the plasma membrane. For example, over the past few years, a new class of potentially fatal cardiac arrhythmias has been linked with cytoplasmic proteins that include sub-membrane adapters such as ankyrin-B (ANK2), ankyrin-G (ANK3), and alpha-1 syntrophin, membrane coat proteins including caveolin-3 (CAV3), signaling platforms including yotiao (AKAP9), and cardiac enzymes (GPD1L). The focus of this review is to detail the exciting role of lamins, yet another class of gene products that have provided elegant new insight into human disease.